2018
DOI: 10.1007/s13193-018-0861-4
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy After Initial Lumpectomy (SNAIL Study)—a Prospective Validation Study

Abstract: Tertiary oncology center clinicians are commonly faced with the problem of managing patients with a diagnosis of breast cancer made after lumpectomy in the Primary Health Care (PHC) setting. There are no studies or guidelines that address the further surgical management in this group of patients regarding sentinel lymph node biopsy (SLNB) and need for breast post-operative cavity excision. Prospective observational study was planned to evaluate the feasibility of SLNB and defining the need for definitive breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This finding is in line with other studies that have shown that more extensive procedures affect successful and accurate SLN detection. 42 The only exception was women who previously underwent WLE. Specifically, nodal concordance between SPIO and Tc 99 in the SentiNot trial was markedly low after OPBCT or mastectomy, meaning that when Tc 99 was successful in detecting a lymph node, it was likely not the sentinel lymph node draining the DCIS/IBC area of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with other studies that have shown that more extensive procedures affect successful and accurate SLN detection. 42 The only exception was women who previously underwent WLE. Specifically, nodal concordance between SPIO and Tc 99 in the SentiNot trial was markedly low after OPBCT or mastectomy, meaning that when Tc 99 was successful in detecting a lymph node, it was likely not the sentinel lymph node draining the DCIS/IBC area of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more attention should be given to the subjective reports of symptom such as reporting self-perceived arm lymphoedema, regardless of objective lymphoedema or not, have a decreased longterm health-related quality of life (66). Although SLNB has great advantages (67), it has false negative rate (FNR) of detecting cancer (68,69) In summary, the combination of contrast-enhanced ultrasonography with blue dye, serial sectioning and other methods can effectively reduce the false negative of SLNB (77,78).…”
Section: Advantages and Disadvantages Of Slnb In Breast Cancermentioning
confidence: 99%